Communication of Da'wah in the Creative Muslim Community: A Study on the Hijrah Yuk Ngaji Community - Yogi Muhammad Yusuf (Jurnal Scientia, 2025)
This study aims to analyze the forms and strategies of da'wah communication implemented within a creative Muslim community, focusing on the Hijrah Yuk Ngaji Community. This community is known as a platform for young people who promote the spirit of da'wah through contemporary approaches and digital media. The research method used is a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document studies. The results of the study show that the Yuk Ngaji Community has successfully implemented effective and adaptive da'wah communication strategies tailored to the characteristics of the younger generation by utilizing various da'wah models such as bil-lisan (verbal preaching), bil-qalam (written preaching), and bil-hal (preaching through actions). This community does not solely rely on lectures or Islamic studies but actively uses social media and digital platforms as the main tools for delivering communicative, relevant, and inspiring da'wah messages. Member involvement in the da'wah process and a structured cadre system further strengthen Yuk Ngaji’s role as a platform for spiritual, intellectual, and social development, thereby enabling the creation of a young Muslim generation that not only comprehensively understands Islamic teachings but also applies them in daily life and contributes positively to their surroundings.